Auricular Cartilage Regeneration with Adipose-Derived Stem Cells in Rabbits - Se-Joon Oh; Hee-Young Park; Kyung-Un Choi; Sung-Won Choi; Sung-Dong Kim; Soo-Keun Kong; Kyu-Sup Cho (Hindawi Limited, 2018)
Tissue engineering cell-based therapy using induced pluripotent stem cells and adipose-derived stem cells (ASCs) may be promising tools for therapeutic applications in tissue engineering because of their abundance, relatively easy harvesting, and high proliferation potential. The purpose of this study was to investigate whether ASCs can promote the auricular cartilage regeneration in the rabbit. In order to assess their differentiation ability, ASCs were injected into the midportion of a surgically created auricular cartilage defect in the rabbit. Control group was injected with normal saline. After 1 month, the resected auricles were examined histopathologically and immunohistochemically. The expression of collagen type II and transforming growth factor-β1 (TGF-β1) were analyzed by quantitative polymerase chain reaction. Histopathology showed islands of new cartilage formation at the site of the surgically induced defect in the ASC group. Furthermore, Masson's trichrome staining and immunohistochemistry for S-100 showed numerous positive chondroblasts. The expression of collagen type II and TGF-β1 were significantly higher in the ASCs than in the control group. In conclusion, ASCs have regenerative effects on the auricular cartilage defect of the rabbit. These effects would be expected to contribute significantly to the regeneration of damaged cartilage tissue in vivo.